Laryngopharyngeal complaints following short-term endotracheal intubation: peculiarities of males and females - PAULAUSKIENĖ, Iveta; LESINSKAS, Eugenijus (Acta medica Lituanica, 2012)
Background. Laryngopharyngeal complaints are classified as minor post-intubation complications. They cause great discomfort, have some influence on the quality of life and can limit patient’s casual activity. The extent of complaints ranges from 12 to 65%. Undesirable complications can be avoided by ascertaining factors that are able to provoke or decrease laryngopharyngeal symptoms after endotracheal intubation. In this study, we assessed predominant laryngopharyngeal symptoms following a short-term endotracheal intubation and their peculiarities subject to gender, and we estimated the most important influencing factors.Materials and methods. 218 patients were examined before endotracheal anesthesia, 1–2 and 24 hours after extubation. The following laryngopharyngeal complaints were recorded: hoarseness, vocal fatigue, globus pharyngeus, throat pain and throat clearing. These factors were also assessed in relation to endotracheal intubation parameters: endotracheal tube size, cuff volume and pressure, number of intubation attempts, length of anesthesia, experience of anesthesiologist and additional parameters: smoking, allergy, GERD symptoms, laryngitis and singing skills subject to gender.Results. All laryngopharyngeal symptoms increased significantly in 2 hours after extubation and remained increased after 24 hours in both male and female groups. In 1–2 hours after extubation, females complained of throat pain more than males (61.3 vs. 42.9%; p = 0,014). The following significant relations were found 1–2 hours after extubation: between throat pain and length of anesthesia, globus pharyngeus and tube size and cuff volume in the male group; between globus pharyngeus, vocal fatigue and smoking, throat clearing and cuff volume in the female group. After 24 hours, the relation was noticed between vocal fatigue and cuff volume and number of intubation attempts, globus pharyngeus and length of anesthesia, between hoarseness and number of intubation attempts and between throat pain and singing skills in the male group. Some relation between throat clearing and cuff volume remained for 24 hours after extubation, smoking had influence on hoarseness and vocal fatigue in the female group.Conclusions. Laryngopharyngeal symptoms remain an important cause of discomfort for 24 hours after extubation. Females complain of laryngeal and pharyngeal symptoms more than males and throat pain following extubation is also more frequent in females. The most important parameters of short-term endotracheal intubation that influence laryngopharyngeal complaints are as follows: cuff volume, length of anesthesia and number of intubation attempts that affect males more than females. Smoking affects females more, though singing skills are more significant in the male group.
Keywords: endotracheal intubation; laryngopharyngeal symptoms; hoarseness; throat pain